Love & war in London : a woman's diary, 1939-1942 - Cockett, Olivia, 1912-1998 (Life writing series., 2005)
Olivia Cockett was twenty-six years old in the summer of 1939 when she responded to an invitation from Mass-Observation to 'ordinary' individuals to keep a diary of their everyday lives, attitudes, feelings, and social relations. This book is an annotated, unabridged edition of her candid and evocative diary.; 'Love and War in London: A Woman's Diary 1939-1942' is rooted in the extraordinary milieu of wartime London. Vibrant and engaging, Olivia's diary reveals her frustrations, fears, pleasures, and self-doubts. She records her mood swings and tries to understand them, and speaks of her lover, a married man, and the intense relationship they have. As she and her friends and family in New Scotland Yard are swept up by the momentous events of another European war, she vividly reports on what she sees and hears in her daily life.; Hers is a diary that brings together the personal and the public. It permits us to understand how one intelligent, imaginative woman struggled to make sense of her life, as the city in which she lived was drawn into the turmoil of a catastrophic war.